Clinical outcomes and adverse events of Hedgehog pathway inhibitors for advanced basal cell carcinoma patients: A systematic review and meta-analysis - Suvijak Untaaveesup; Wichapol Dendumrongsup; Pornteera Srichana; Chanamon Pongphaew; Gynna Techataweewan; Kanmanee Viratkapan; Nichanant Nampipat; Ben Ponvilawan; Chayanis Kositamongkol; Walaiorn Pratchyapruit; Pochamana Phisalprapa (Heliyon)
Background: Basal cell carcinoma (BCC) is the most common form of skin cancer and poses treatment challenges in advanced stages. Treatment options include surgery, radiotherapy, and systemic therapies, but tumor location and prior interventions can limit these methods. Hedgehog pathway inhibitors (HPIs) are used for patients unsuitable for conventional treatments. Objective: This meta-analysis evaluated the effectiveness and safety profile of HPIs in managing advanced BCC. Methods: We conducted a comprehensive literature review across Embase, Scopus, PubMed, and the Cochrane Central Register of Controlled Trials databases from inception until March 2024. The focus was on the effectiveness and safety of HPIs, with or without adjunct surgery or radiotherapy. Pooled objective response rates (ORRs) and 95% confidence intervals (CIs) were calculated using inverse variance random-effects models. Results: The analysis comprised 16 studies, including 14 retrospective cohort studies, one prospective cohort study, and one randomized controlled trial, with 1689 participants. The pooled ORR for HPIs was 73% (95% CI 63%–82%; I2 = 93%) across all stages of the disease. For locally advanced disease, the ORR was 63% (95% CI 49%–75%; I2 = 89%), while for metastatic disease, it was 25% (95% CI 14%–40%; I2 = 19%). No significant differences were found in the effectiveness of different HPIs. ORRs ranged from 25% to 89% for patients who underwent surgery or radiotherapy. Conclusions: This meta-analysis indicates that HPIs are more beneficial in treating locally advanced BCC than metastatic disease. No statistically significant differences were found in the effectiveness among various HPIs.